Effect of working temperature on the interfacial behavior of overmolded hybrid fiber reinforced polypropylene composites. (November 2020) - Fu, Liang; Ding, Yudong; Weng, Can; Zhai, Zhanyu; Jiang, Bingyan
Abstract: In the present study, the interfacial behavior of overmolded hybrid fiber reinforced polypropylene composites (hybrid composites) in the working temperature range from 23 °C to 90 °C was studied by experimental and constitutive methods. Monotonic and cycle loading-unloading single-lap-shear tests were employed to determine the interfacial properties of hybrid composites. The experimental results show that both interfacial shear strength and shear stiffness decrease with increasing working temperature. A regression function was adopted to evaluate the decaying degree of interfacial properties with increasing working temperature. The shear stress-displacement relationship under monotonic loading exhibits nonlinear behavior after an initial elastic region. The envelope lines of shear stress-displacement of hybrid composites under cyclic loading indicate that the nonlinearity in the curve is caused by the plastic deformation of polypropylene in the interphase region. A constitutive model was built to describe the nonlinear shear stress-displacement relation of hybrid composites at different working temperatures. A full suite of temperature-dependent plastic parameters in the model was obtained from cyclic loading-unloading tensile tests. The predicted shear stress–displacement curves agreed well with experimental results from different working temperatures. In addition, the failure mode of hybrid composites varied with working temperature. Highlights: The interfacial behavior of overmolded hybrid composites under different working temperatures are investigated. The interfacial stress and shear stiffness decrease with increasing working temperature. The interfacial failure mechanism evolves with working temperature. A temperature-dependent nonlinear constitutive model for hybrid composites is built.